2016
DOI: 10.21767/2476-1974.100008
|View full text |Cite
|
Sign up to set email alerts
|

NF-kB Regulation in T-cells in Pregnancy is Mediated via Fas/FasL Interactions: The Signal for which is Derived from Exosomes Present in Maternal Plasma

Abstract: Background: Regulated suppression of maternal Th1 immunity is necessary for normal pregnancy since inappropriate Th1 responses results in increased pregnancy loss and complications including intrauterine growth restriction (IUGR). We have shown that suppression of the p65 subunit of NF-κB in maternal T-cells underlies this change in T-cell responses. This study aimed to determine mechanism(s) that control p65 suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
0
13
0
2
Order By: Relevance
“…McCracken et al. note that FasL+ exosomes in maternal plasma regulate NF κ B levels in circulating maternal T cells through Fas activation . The activation of Fas, a type‐I transmembrane protein of T cells, by exsosomal FasL results in the creation of a suitable cytokine profile for pregnancy by the suppression of NF κ B (Figure ).…”
Section: Nfκb and The Maintenance Of Pregnancymentioning
confidence: 99%
“…McCracken et al. note that FasL+ exosomes in maternal plasma regulate NF κ B levels in circulating maternal T cells through Fas activation . The activation of Fas, a type‐I transmembrane protein of T cells, by exsosomal FasL results in the creation of a suitable cytokine profile for pregnancy by the suppression of NF κ B (Figure ).…”
Section: Nfκb and The Maintenance Of Pregnancymentioning
confidence: 99%
“…Dr McCracken has shown that the signal that facilitates the suppression of Th1 immunity is derived from pregnancy specific exosomes present in maternal plasma [5]. Placental exosomes possess immune suppressive properties via enhancing lymphocyte apoptosis and suppressing CD3ζ expression, a signalling moiety required for T-cell receptor activation [5,6].…”
mentioning
confidence: 99%
“…Placental exosomes possess immune suppressive properties via enhancing lymphocyte apoptosis and suppressing CD3ζ expression, a signalling moiety required for T-cell receptor activation [5,6]. Exosomes derived specifically from placental cultures express ULBP1-5 and Major histopatibility complex 1 and 2 on their surface and induced down-regulation of the NKG2D receptor on NK, CD8(+) cells and gamma delta T cells, leading to reduction of their in vitro cytotoxicity [7] which in vivo would ultimately lead to fetal sparing.…”
mentioning
confidence: 99%
“…They have shown that cows with higher conception rates have the GA polymorphism in the FLI-1 5' untranslated region and express higher levels of FLI-1 transcripts with the GA polymorphism. Furthermore, they have shown that cows with the deletion polymorphism had lower conception rate after embryo transfer and had higher serum levels of perforin, a product of natural killer cells, which might have contributed to the lower conception rate in these animals.McCracken and colleagues [2] have discovered a potential mechanism of suppression of the maternal Th1 immunity during normal pregnancy. They have shown that pregnancy derived Fas ligand (FasL) exosomes in maternal plasma regulate p65 levels in circulating T-cells through Fas activation, and that the suppression of p65 subunit of the nuclear factor kappa-lightchain-enhancer of activated B cells (NF-kB) in T-cells underlies the suppression of maternal Th1 immunity during pregnancy.…”
mentioning
confidence: 99%
“…McCracken and colleagues [2] have discovered a potential mechanism of suppression of the maternal Th1 immunity during normal pregnancy. They have shown that pregnancy derived Fas ligand (FasL) exosomes in maternal plasma regulate p65 levels in circulating T-cells through Fas activation, and that the suppression of p65 subunit of the nuclear factor kappa-lightchain-enhancer of activated B cells (NF-kB) in T-cells underlies the suppression of maternal Th1 immunity during pregnancy.…”
mentioning
confidence: 99%